Self and World in Schopenhauer's Philosophy. - Janaway, Christopher (Oxford University Press, UK, 1989)
Christopher Janaway presents the first full-length study of Arthur Schopenhauer's central philosophical achievement: his account of the self and its relation to the world of objects. Schopenhauer's dynamic system of thought embraces epistemological, metaphysical, psychological, and physiological concerns; Janaway gives a clear and careful guide to this system, and shows that it offers much illumination for current philosophical work on the self.